Testing of Weakly Weathered Granites of Different Porosities Using a Split Hopkinson Pressure Bar Technique - Lei Yan; Liansheng Liu; Shenghui Zhang; Depei Lan; Jiangchao Liu (Advances in Civil Engineering)
Nuclear magnetic resonance (NMR) and damage impact testing, using a split Hopkinson pressure bar (SHPB) technique, were conducted on weakly weathered granites of different porosities. Based on this, this study determined and analysed the pore structure and distribution, propagation characteristics of stress waves, changes in initial tangent modulus, and energy dissipation in weakly weathered granites of different porosities. The research demonstrated that the nature of the internal porosity of weakly weathered granites changed with total porosity. Pore structure significantly influenced the amplitude of reflected waves and distortion of transmitted waves. Under constant-damage impact loads, the initial tangent modulus decreased with increasing porosity, whereas the stress-strain curves, after reaching the peak stress, had similar shapes. Peak stress and average strain rate showed a strong power-law correlation with porosity, and peak stress decreased in a power-law correlation with the increase of average strain rate. In other words, the difference in average strain resulted from different porosities when the incident energy was same, and the average strain was negatively correlated with porosity. Under damaging impact, the energy absorbed per unit volume decreased with increasing porosity. The research results reveal dynamic characteristics of natural porous rocks under damage impacts, which provide a reference for studying damage effects of porous rocks under the effects of stress waves.